2023
DOI: 10.3390/ijms24129786
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Pathogenicity and Causativity of Variants in the MPZ and SH3TC2 Genes in a Family Case of Hereditary Peripheral Neuropathy

Abstract: The implementation of NGS methods into clinical practice allowed researchers effectively to establish the molecular cause of a disorder in cases of a genetically heterogeneous pathology. In cases of several potentially causative variants, we need additional analysis that can help in choosing a proper causative variant. In the current study, we described a family case of hereditary motor and sensory neuropathy (HMSN) type 1 (Charcot–Marie–Tooth disease). DNA analysis revealed two variants in the SH3TC2 gene (c.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…In the current study, this variant was observed in two Russian families in a compound heterozygous state. In one family with two affected siblings the variant co-occurred with the variant c.1177 + 5G>A ( Shchagina et al, 2023 ) ClinVar: [VCV000575267.10]. In another unrelated proband, this variant was found in a compound heterozygous state with a novel single-nucleotide duplication c.3157dup (p. (Leu1053Profs*36)).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the current study, this variant was observed in two Russian families in a compound heterozygous state. In one family with two affected siblings the variant co-occurred with the variant c.1177 + 5G>A ( Shchagina et al, 2023 ) ClinVar: [VCV000575267.10]. In another unrelated proband, this variant was found in a compound heterozygous state with a novel single-nucleotide duplication c.3157dup (p. (Leu1053Profs*36)).…”
Section: Resultsmentioning
confidence: 99%
“…In another family (3514), the disease was caused by variants affecting splicing. c.1177 + 5G>A variant leads to the total absence of the normal transcript ( Shchagina et al, 2023 ). The c.279G>A variant has previously been shown to affect splicing, leading to the insertion of 19 nucleotides from intron 3 with the formation of a premature stop codon TAA in position 127 in the amino acid sequence ( Laššuthová et al, 2012 ).…”
Section: Resultsmentioning
confidence: 99%
“…These variants typically lead to one or more mis-splicing events that result in the skipping of partial or complete exons, and/or the retention of partial or complete introns 2142 . Pathogenic splicing variants have been found in several CMT genes including MPZ 21,30,39,40 , MFN2 22,30,31 , LRSAM1 23 , IGHMBP2 24 , INF2 25 , MCM3AP 26 , SH3TC2 30,32,38 , GDAP1 27,42 , SBF1 28 , NDRG1 37 , and FGD4 29 . Variants affecting canonical splice donor and acceptor sites have also been described in MME 4,41 .…”
Section: Introductionmentioning
confidence: 99%
“…In another family (3514), the disease was caused by variants affecting splicing. c.1177 + 5G>A variant leads to the total absence of the normal transcript (Shchagina et al, 2023). The c.279G>A variant has previously been shown to affect splicing, leading to the insertion of 19 nucleotides from intron 3 with the formation of a premature stop codon TAA in position 127 in the amino acid sequence (Laššuthová et al, 2012).…”
Section: Resultsmentioning
confidence: 99%